Estudio de factibilidad para implementar una microempresa dedicada a la elaboración y comercialización de harina de fruta de pan - Barzola Torres, Maria Jose (2023)
The main objective of this research study was to carry out a feasibility study to implement a micro-enterprise for the production and commercialization of breadfruit flour in the canton of Riobamba. Breadfruit flour can be an alternative to other types of flour for people with nutritional and digestive problems. Which would allow the use of this little-known fruit. This flour is rich in carbohydrates, minerals, and protein necessary for the generation of energy, in addition, this product does not contain gluten, which makes it suitable for people with coeliac disease, i.e. people intolerant to this protein, and it is also suitable for people who wish to improve their diet or lifestyle to a healthier one. The methodology used was qualitative and quantitative, evidenced in the application of surveys, where the information obtained was numerical data with a product acceptance of 63 % and others that allowed to know the appreciation of respondents to the idea. The descriptive methodology was also present, allowing the data studied in the investment to be detailed in narrative, numerical, and graphic form. The 4Ps were analyzed to determine the best marketing plan. As a result, a feasible and profitable project was obtained with an investment of $62.806.02, generating a positive NPV of $25.428.76, which gives way to an Internal Rate of Return of 23.27 %. In the same way, a cost-benefit of 1.40 was obtained; the PRC is 3 years, 9 months, and 17 days.